(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2026)
Maratha funerary monuments chhatris (cenotaphs) and samadhis (memorial platforms) exemplify a distinct commemorative architecture shaped by syncretic influences and dynastic identities. This study investigates their evolution, analysing key examples from prominent Maratha dynasties (Bhosales, Holkars, Scindias, Peshwas) and comparing them with Rajput cenotaphs and Indo-Islamic tomb traditions. Primary survey of the Bhosale Rajghat in Nagpur, combined with extensive photographic surveys and archival research, reveals how Maratha memorials integrate Hindu symbolism (e.g., Shivalingam, Tulsi Vrindavan) with architectural idioms adapted from Deccan Sultanate and Rajput practices. Early Maratha structures mirrored Sultanate tombs with domes and arched kiosks resembling sarcophagi, while later examples evolved into temple-like pavilions with shikharas, mandapas, and guardian icons (dwarapalas). Maratha rulers appropriated funerary customs to legitimize power and honour ancestors, resulting in a typology that diverges from Islamic burials by focusing solely on memorialization, not interment. Results show regional variations: Nagpur’s Bhosales built shrine-like chhatris on cremation sites; Holkars in Indore/Maheshwar blended Rajput aesthetics; Scindias of Gwalior incorporated Mughal elements; Peshwas maintained austere yet ritually functional Samadhis. The discussion infers these findings in terms of religious syncretism, ancestral veneration (dharma and moksha), gender distinctions (e.g., queens’ memorials with Tulsi plants), and political symbolism. Maratha chhatris and samadhis can be understood as layered architectural expressions shaped by long-term regional continuities and interactions. The spatial articulation and formal vocabulary represent a distinctive place within India’s tradition of royal commemorative architecture.